Penjara Nagari sebagai Hukuman Adat dan Upaya Masyarakat Nagari Tigo Jangko dalam Menanggulangi Perzinaan - Salma Salma; Solihin Solihin (Islamica: Jurnal Studi Keislaman, 2015)
This article deals with Penjara Nagari as a place to quarantine a couple who committed an adultery or fornication in Nagari Tigo Jangko. The study attempts to explore the reasons of the people to build a jail, regardless the existing government?s jails. The research found that the Penjara Nagari was built based on the decision of the kerapatan adat to anticipate and educate people to avoid adultery and fornication which were forbidden by Islamic law and Minangkabau tradition. The people caught the couple directly at the location. They screamed, humiliated and hit them. Then they brought the couple to the Penjara Nagari and few of people interrogated the couple and let the other people saw them in the jail. The prisoning of the couple had continued until kerapatan adat had made a decision which contained some punishments for the couple. Usually the prisoning occurred all night long till morning. Penjara Nagari in Islamic and Indonesian legal perspective was not real jail, since the real jail was built for prisoners who got a justice procedure and punishment from the court.